2009
DOI: 10.1158/1078-0432.ccr-09-1245
|View full text |Cite
|
Sign up to set email alerts
|

ABT-888 Confers BroadIn vivoActivity in Combination with Temozolomide in Diverse Tumors

Abstract: Purpose: ABT-888, currently in phase 2 trials, is a potent oral poly(ADP-ribose) polymerase inhibitor that enhances the activity of multiple DNA-damaging agents, including temozolomide (TMZ). We investigated ABT-888+TMZ combination therapy in multiple xenograft models representing various human tumors having different responses to TMZ. Experimental Design: ABT-888+TMZ efficacy in xenograft tumors implanted in subcutaneous, orthotopic, and metastatic sites was assessed by tumor burden, expression of poly(ADP-ri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 43 publications
4
92
0
Order By: Relevance
“…In addition, the doses of veliparib that are sufficient to produce antitumor activity have been shown to be pharmacodynamically active, leading to significant inhibition of PAR levels in vivo (8,31,35,36). Consistent with our previous reports, temozolomide monotherapy at 50 mg/kg/d (i.p., once daily for 5 days) produced significant tumor growth inhibition (45% TGI at day 14) when compared with the vehicle group (Fig.…”
Section: Activity In Xenograft Tumor Modelssupporting
confidence: 89%
See 2 more Smart Citations
“…In addition, the doses of veliparib that are sufficient to produce antitumor activity have been shown to be pharmacodynamically active, leading to significant inhibition of PAR levels in vivo (8,31,35,36). Consistent with our previous reports, temozolomide monotherapy at 50 mg/kg/d (i.p., once daily for 5 days) produced significant tumor growth inhibition (45% TGI at day 14) when compared with the vehicle group (Fig.…”
Section: Activity In Xenograft Tumor Modelssupporting
confidence: 89%
“…We and other researchers have shown previously that PARP inhibitors can effectively potentiate the activity of temozolomide in various xenograft models (7,8,31,34). In addition, the doses of veliparib that are sufficient to produce antitumor activity have been shown to be pharmacodynamically active, leading to significant inhibition of PAR levels in vivo (8,31,35,36).…”
Section: Activity In Xenograft Tumor Modelsmentioning
confidence: 92%
See 1 more Smart Citation
“…1) is a novel and potent inhibitor of PARP-1 and PARP-2 enzymes (K i of 5 and 2 nM, respectively) and has demonstrated excellent in vivo efficacy in a broad spectrum of preclinical tumor models in combination with a variety of cytotoxic agents such as temozolomide (TMZ), cisplatin, cyclophosphamide, and radiation (Donawho et al, 2007;Palma et al, 2009;Penning et al, 2009). Preclinical pharmacokinetic profiles of veliparib were characterized by high plasma clearance, high volumes of distribution, and high oral bioavailability across species (Donawho et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that PARP inhibitors might function as sensitizing agents for chemotherapy and radiotherapy that cause DNA damage [26]. Palma et al have shown what they called "potent antitumor efficacy" of the PARP inhibitor, ABT-888 with temozolomide (TMZ) in orthotopic and metastatic implantation models across a spectrum of histologic types.Their results are worth noting, because the efficacy was independent of TMZ activity and overcame both inherent and acquired TMZ resistance [27]. Japanese investigators found that adding olaparib to SN-38 or irinotecan potentiated S-phase double-strand breaks, producing a synergistic effect in cells that were MSI-H and non-MSI-H [28].…”
Section: Discussionmentioning
confidence: 98%